Seasonal variations of mineralogical and chemical composition of particulate matter in a large boreal river and its tributaries - Kritskov, Ivan V.; Lim, Artem G.; Shevchenko, Vladimir P.; Starodymova, Dina P.; Dara, Olga M.; Kolesnichenko, Yuri Y.; Zinchenko, Dmitri O.; Vorobyev, Sergey N. биолог; Pokrovsky, Oleg S. (Water)
Despite the importance of river suspended matter (RSM) for carbon, nutrient, and trace metal transfer from the land to the ocean, the mineralogical control on major and trace element speciation in the RSM remains poorly constrained. To gain a better understanding of environmental and seasonal factors controlling the mineral and chemical composition of riverine suspended load, we studied, over several hydrological seasons, including winter baseflow, the RSM of a large boreal river in Western Siberia (Ob in its middle course) and its two small tributaries. The concentration of RSM increased from 2–18 mg/L in winter to 15–105 mg L−1 during the spring flood. Among the dominant mineral phases of the RSM in the Ob River, quartz (20–40%), albite (4–18%), smectite (2–14%), and chlorite (6–16%) increased their relative proportions with an increase in discharge in the order “winter ≤ summer < spring flood”; illite (5–15%) was not affected by seasons or discharge, whereas the abundance of calcite (0–30%) decreased with discharge, from winter to summer and spring. Seasonal variation of elemental composition of the Ob River’s RSM allowed distinguishing three main groups of elements. Sodium, K, Si, Al, trivalent, and tetravalent hydrolysates increased their concentrations in the RSM with an increase in discharge, reflecting enhanced contribution of lithogenic material during high flow, whereas the concentration of alkaline-earth metals (Ca, Sr, Ba), P, Mn, and As decreased with discharge, reflecting accumulation of these elements in the suspended matter under ice. At the same time, a number of nutrients and trace elements demonstrated progressive accumulation in the RSM during winter (Ca, P, Cu, Zn, Mo, As, Cd, Sb). Micronutrients (V, Co), Fe, and Cr exhibited a minimum during summer, which could reflect both the uptake of these elements by the biota during baseflow (micronutrients) and their enhanced export during winter and spring compared to summer (Fe). The RSM of small tributaries demonstrated quite a different pattern compared to the Ob River main stem. Maximal concentration of suspended matter was observed at low discharges during the winter. During this period, the RSM was dominated by amorphous Fe hydroxides. Overall, the obtained results confirm the overwhelming impact of peatlands on element export in suspended form in small rivers of Western Siberia, and strong seasonal variations of both mineralogy and chemistry of the RSM in the Ob River main stem. Elemental yields (watershed-normalized export), assessed for the first time for the middle course of the Ob River and tributaries, were shifted towards the more important role of particulate vs. dissolved export for a number of trace elements, compared to that of the small and medium-sized rivers of Western Siberia, draining the taiga forest and peatlands of the boreal zone. The contrasting pattern of RSM chemical composition across the year demonstrated the importance of seasonal approach for sampling river suspended matter and calls a need for addressing strongly understudied RSM sources during winter baseflow, under ice.